Application of Fibronectin-Coated Microparticles for Isolation of Human iPSC-Derived MSCs - Jae Hyeok Jang; In Sun Hwang; Ji Seob Kim; Sunjun Lee; Min Hee Moon; Bowon Kim; Seo Jeong Kim; Jongho Choi; Young Her; Soo-Hong Lee; Byung-Hyun Cha (Tissue Engineering and Regenerative Medicine, 2026)
BACKGROUND : Bone marrow–derived MSCs (BMMSCs) are limited by availability, donor variability, and age-related decline, highlighting the need for alternative MSC sources. Induced pluripotent stem cells (iPSCs) offer a scalable solution. This study introduces a novel three-dimensional culture platform based on fibronectin (FN)-coated microparticles to efficiently derive and expand human iPSC-derived MSCs (iMSCs). METHODS : The system utilizes FN-coated non-porous (CytoDex) and porous (CytoPore) microparticles. FN coating efficacy on microparticle was confirmed using Rhodamine-labeled FN and confocal microscope. Base on various molecular cell biological experiment, the utilization of FN-coated CytoDex and CytoPore leverages an expanded surface area to improve iMSCs isolation. The characteristics and cell behaviors of iMSCs generated from FN-coated CytoDex and CytoPore was evaluated by immunophenotype analysis, cell proliferation, and senescence related assays. In vivo tissue regeneration was evaluated by microcomputed tomography and histopathological analyses. RESULTS : The porous microparticle CytoPore significantly enhanced FN coating efficiency, cell attachment, and proliferation compared to CytoDex. FN-coated CytoPore enabled the selective isolation of a high-purity MSC population from spontaneously differentiated iPSCs (SD-iPSCs) by day 7, confirmed by distinct morphology and mesodermal marker expression. The resulting iMSCs exhibited immunophenotypic characteristics comparable to adult MSCs, along with superior proliferative capacity, extended telomere length, and minimal senescence over 10 passages, in contrast to BMMSCs. Furthermore, iMSCs demonstrated effective in vivo tissue regeneration in an osteochondral defect model. CONCLUSION : This novel FN-coated microparticle-based 3D culture platform enables efficient, large-scale production of high-quality iMSCs and holds strong potential for clinical applications in stem cell therapeutics and regenerative medicine.

Immunomodulation Effects of Porcine Cartilage Acellularized Matrix (pCAM) for Osteoarthritis Treatment - Ji Seob Kim; Hyeon Jae Kwon; In Sun Hwang; Young Hwa Lee; Kyung-Noh Yoon; Hee-Woong Yun; Jae-Hyeok Jang; Seo Jeong Kim; Zhoodatova Aiana; Seungwoo Kim; Minhee Moon; Bongki Kim; et al. (Tissue Engineering and Regenerative Medicine, 2025)

Signal-off colorimetric and signal-on fluorometric dual-mode aptasensor for ultrasensitive detection of Salmonella Typhimurium using graphitic carbon nitride - Thinh Viet Dang; In Seung Jang; Quynh Huong Nguyen; Hyeun Seok Choi; Byung Jo Yu; Moon Il Kim (Food Chemistry, 2025)

A comparison of the nutritional quality of ready-to-cook meals and conventional home-cooked meals in Korea - Eunji Choi; Sung-Won Yoon; Jung-Ah Shin; In-Hwan Kim; Jeehye Sung; Jang-Hyuk Ahn; Hyun-Jeong Kim; Dong Won Seo; Sam-Pin Lee; Jo-Won Lee; Bo Kyung Moon; Sojung Kim; et al. (International Journal of Gastronomy and Food Science, 2024)

Comparison of the clinical characteristics and outcomes of bloodstream infections caused by Raoultella species and Klebsiella pneumoniae - Kyung-Wook Hong; Yun-Hong Cheon; Kyunglan Moon; Sun In Hong; Byung-Han Ryu; Oh-Hyun Cho; In-Gyu Bae (Infectious Diseases, 2020)

Cytokeratin 18 is necessary for initiation of TGF-β1-induced epithelial–mesenchymal transition in breast epithelial cells - Hyejung Jung; Bomin Kim; Byung In Moon; Eok-Soo Oh (Molecular and Cellular Biochemistry, 2016)

Dietary aflatoxin B1 intake, genetic polymorphisms of CYP1A2, CYP2E1, EPHX1, GSTM1, and GSTT1, and gastric cancer risk in Korean - Sang-Yong Eom; Dong-Hyuk Yim; Yanwei Zhang; Jung-Kuk Yun; Sun In Moon; Hyo-Yung Yun; Young-Jin Song; Sei-Jin Youn; Taisun Hyun; Joo-Seung Park; Byung Sik Kim; Jong-Young Lee; et al. (Cancer Causes & Control, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Source of low frequency modulation of ENSO amplitude in a CGCM - Byung-Kwon Moon; Sang-Wook Yeh; Boris Dewitte; Jong-Ghap Jhun; In-Sik Kang (Climate Dynamics, 2007)

Improving the dynamic response of a mediator-less microbial fuel cell as a biochemical oxygen demand (BOD) sensor - Hyunsoo Moon; In Seop Chang; Kui Hyun Kang; Jae Kyung Jang; Byung Hong Kim (Biotechnology Letters, 2004)

A microbial fuel cell with improved cathode reaction as a low biochemical oxygen demand sensor - Kui Hyun Kang; Jae Kyung Jang; The Hai Pham; Hyunsoo Moon; In Seop Chang; Byung Hong Kim (Biotechnology Letters, 2003)